All Future Plunges to the Past : James Joyce in Russian Literature - Vergara, Jose, 1988- (Book collections on Project MUSE., 2021)
"Examines Russian literary responses to James Joyce through a series of case studies: the novels of Yury Olesha, Vladimir Nabokov, Andrei Bitov, Sasha Sokolov, and Mikhail Shishkin. It considers their intertextual relationships to Joyce, their contexts, and Joyce's shifting role in Russia from 1927 to the present day"--